Radiogenic heating and craton‐margin plate stresses as drivers for intraplate orogeny. (4th May 2017) - Korhonen, F. J.; Johnson, S. P.; Wingate, M. T. D.; Kirkland, C. L.; Fletcher, I. R.; Dunkley, D. J.; Roberts, M. P.; Sheppard, S.; Muhling, J. R.; Rasmussen, B.
ABSTRACT: The Proterozoic belts that occur along the margins of the West Australian Craton, as well as those in intraplate settings, generally share similar geological histories that suggest a common plate‐margin driver for orogeny. However, the thermal drivers for intraplate orogenesis are more poorly understood. The Mutherbukin Tectonic Event records a protracted period of Mesoproterozoic reworking of the Capricorn Orogen and offers significant insight into both the tectonic drivers and heat sources of long‐lived intraplate orogens. Mineral assemblages and tectonic fabrics related to this event occur within a 50 km‐wide fault‐bound corridor in the central part of the Gascoyne Province in Western Australia. This zone preserves a crustal profile, with greenschist facies rocks in the north grading to upper amphibolite facies rocks in the south. The P – T – t evolution of 13 samples from 10 localities across the Mutherbukin Zone is investigated using phase equilibria modelling integrated with in situ U–Pb monazite and zircon geochronology. Garnet chemistry from selected samples is used to further refine the P–T history and shows that the dominant events recorded in this zone are prolonged D1 transpression between c . 1, 320 and 1, 270 Ma, followed by D2 transtension from c . 1, 210 to 1, 170 Ma. Peak metamorphic conditions in the mid‐crust reached >650°C and 4.4–7 kbar at c . 1, 210–1, 200 Ma. Most samples record a single clockwise P–T evolution during this event, although some samples might have experienced multiple perturbations. The heat source for metamorphism was primarily conductive heating of radiogenic mid‐ and upper crust, derived from earlier crustal differentiation events. This crust was thickened during D1 transpression, although the thermal effects persisted longer than the deformation event. Peak metamorphism was terminated by D2 transtension at c . 1, 210 Ma, with subsequent cooling driven by thinning of the radiogenic crust. The coincidence of a sedimentary basin acting as a thermal lid and a highly radiogenic mid‐crustal batholith restricted to the Mutherbukin Zone accounts for reworking being confined to a discrete crustal corridor. Our results show that radiogenic regions in the shallow to mid crust can elevate the thermal gradient and localize deformation, causing the crust to be more responsive to far‐field stresses. The Mutherbukin Tectonic Event in the Capricorn Orogen was synchronous with numerous Mesoproterozoic events around the West Australian Craton, suggesting that thick cratonic roots play an important role in propagating stresses generated at distant plate boundaries.